1998
DOI: 10.1001/archinte.158.8.925
|View full text |Cite
|
Sign up to set email alerts
|

Survival After Massive (>2000) Africanized Honeybee Stings

Abstract: We report the clinical case of a man who survived a massive attack of Africanized bees (>2000 bee stings). The man experienced anaphylactic shock and multisystem organ failure (neurologic, hepatic, renal, and hematologic failure). He was treated with administration of dopamine hydrochloride, antihistaminic agents, corticosteroids, fluid and electrolyte replenishment, peritoneal dialysis, and plasmapheresis. No sequelae have been observed during follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 5 publications
1
22
0
2
Order By: Relevance
“…SLED offers the advantages of flexible timing of treatment and reduced costs with the added benefit of unrestricted physician access to the patient during the day, minimizing the interference of renal replacement therapy with other intensive care unit activities, therefore it is better to replace CVVH with SLED when the patient's condition becomes stable. In our 2 cases, repeated CT scans indicated that APE disappeared after 5 and 3 days of intervention by HRRT, and renal function completely recovered after 22 and 37 days, respectively, which was faster than when the patients were treated by intermittent hemodialysis or peritoneal dialysis (1-3 months) as reported previously [5] .…”
supporting
confidence: 80%
“…SLED offers the advantages of flexible timing of treatment and reduced costs with the added benefit of unrestricted physician access to the patient during the day, minimizing the interference of renal replacement therapy with other intensive care unit activities, therefore it is better to replace CVVH with SLED when the patient's condition becomes stable. In our 2 cases, repeated CT scans indicated that APE disappeared after 5 and 3 days of intervention by HRRT, and renal function completely recovered after 22 and 37 days, respectively, which was faster than when the patients were treated by intermittent hemodialysis or peritoneal dialysis (1-3 months) as reported previously [5] .…”
supporting
confidence: 80%
“…Massive attacks by honeybees have been reported in studies from different parts of the world and there is a consensus that severe complications as arterial hypotension, hemolysis, rhabdomyolysis, coagulation disturbance and hepatic involvement are directly related to the number of stings 2,3,9,19 . Systemic toxic effects of bee venom are generally seen on patients with more than 50 stings 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Systemic toxic effects of bee venom are generally seen on patients with more than 50 stings 19 . The potentially lethal number of stings has been estimated at 500, and death is probably due to a direct systemic effect of the venom 2 . The most frequent clinical findings seen in these cases were generalized edema, arterial hypotension, hemolysis, rhabdomyolysis and acute renal failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their colonies are installed in houses, walls and trees, which indicates a high degree of synanthropism (7). Hence, the number of accidents caused by bee stings has increased in recent years (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Escher et al (18) and Malaspina et al (19) reported a large number of patients treated in emergency centers in São Paulo state, affected by allergic reactions to Hymenoptera venom, and observed that 32% of them were victims of bee stings, 37% of wasp stings and 31% of ant stings.…”
mentioning
confidence: 99%